Implementation Of Civil Education As Character Education In Schools - Rinita Rosalinda Dewi; Sofyan Sauri; Aceng Kosasih (Universitas of Muhammadiyah Makassar, 2021)
Abstract. This study aims to determine how the implementation of civic education as character education in schools, especially at SDN 077 Sejahtera, Bandung. The research focus is on religious character, national spirit, curiosity, responsibility, friendly/communicative, and hard work. This study used a qualitative descriptive-analytical method. The instruments used were observation, interview, and documentation study. The results of this study indicate that (1) Planning the implementation of civic education as character education in schools, especially SDN 077 Sejahtera, has been prepared in learning planning, namely in syllabus and character lesson plans. (2) The implementation of civic education as character education in schools, especially at SDN 077 Sejahtera, namely Civics teachers have implemented and used various learning methods and resources and integrated various characters in activities. (3) Evaluation of the implementation of civic education as character education in schools, especially at SDN 077 Sejahtera, namely the teacher has carried out various assessments such as written tests but is still not maximal in assessing the attitudes of students during the learning process. (4) The constraints on the implementation of civic education as character education in schools, especially at SDN 077 Sejahtera are that learning time is considered very fast so that the assessment of student attitudes is not optimal, and character education at home is lacking, so that character education in schools is also less than optimal.Keywords: Civic Education; Character Education; SchoolAbstrak. Penelitian ini bertujuan untuk mengetahui bagaimanakah Implementasi Pendidikan Kewarganegaraan sebagai sebagai Pendidikan Karakter di Persekolahan khususnya di SDN 077 Sejahtera, Bandung. Adapun fokus penelitian pada karakter religius, semangat kebangsaan, rasa ingin tahu, tanggung jawab, bersahabat/komunikatif dan kerja keras. Penelitian ini menggunakan metode kualitatif deskrptif analitis. Instrumen yang digunakan observasi, wawancara, dan studi dokumentasi. Hasil penelitian ini menunjukkan bahwa (1) perencanaan implementasi pendidikan keawarganegaraan sebagai pendidikan karakter di persekolahan khususnya di SDN 077 Sejahtera telah disiapkan dalam perencanaan pembelajaran yaitu dalam silabus dan RPP berkarakter. (2) pelaksanaan implementasi pendidikan kewarganegaraan sebagai pendidikan karakter di persekolahan khususnya di SDN 077 Sejahtera yaitu guru PKn telah menerapkan dan menggunakan metode dan sumber belajar yang beragam serta mengintegrasikan berbagai karakter dalam kegiatan. (3) Evaluasi implementasi pendidikan kewarganegaraan sebagai pendidikan karakter di persekolahan khususnya di SDN 077 Sejahtera yaitu guru telah melakukan berbagai penilaian seperti tes tulis, tetapi masih kurang maksimal dalam melakukan penilaian terhadap sikap peserta didik selama proses pembelajaran. (4) Kendala implementasi pendidikan kewarganegaraan sebagai pendidikan karakter di persekolahan khususnya di SDN 077 Sejahtera adalah waktu pembelajaran dianggap sangat cepat, sehingga penilaian terhadap sikap siswa kurang optimal, dan pendidikan karakter dirumah yang kurang, sehingga pendidikan karakter di sekolah juga kurang optimal.Kata Kunci: Pendidikan kewarganegaraan, Pendidikan karakter,Sekolah